2009
DOI: 10.3171/2009.2.peds08149
|View full text |Cite
|
Sign up to set email alerts
|

Screw fixation of the upper cervical spine in the pediatric population

Abstract: Object Rigid fixation of the upper cervical spine has become an established method of durable stabilization for a variety of craniocervical pathological entities in children. In children, specifically, the use of C1–2 transarticular screws has been proposed in recent literature to be the gold standard configuration for pathology involving these levels. The authors reviewed the use of rigid fixation techniques alternative to C1–2 transarticular screws in children. Fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 28 publications
1
39
0
6
Order By: Relevance
“…One patient sustained injury to the vertebral artery. Similarly, Haque et al [11] reported on four O-C fusion cases with a C1 lateral mass screw, C2 pars screw, and laminar screw. These patients did not have any significant morbidity associated with the procedure and all achieved solid fusion.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…One patient sustained injury to the vertebral artery. Similarly, Haque et al [11] reported on four O-C fusion cases with a C1 lateral mass screw, C2 pars screw, and laminar screw. These patients did not have any significant morbidity associated with the procedure and all achieved solid fusion.…”
Section: Discussionmentioning
confidence: 90%
“…C1-2 transarticular screw fixation (Magerl technique [3]) and its effectiveness in pediatric patients have been described [8,16,17]. Similarly, some studies reported that the C1 lateral screw and C2 pedicle screw technique (Goel-Harms constructs [4,5]) provide stabilization and promotes fusion in pediatric patients with AAI [9][10][11][12][13]. Also, unlike wiring techniques, C1-2 transarticular screw and Goel-Harms constructs do not require that the patient be placed in a halo vest postoperatively [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2). The routine depth of screws in the lateral mass has been shown to be possible up to 20 mm in children [10]. We use lateral fluoroscopy to determine the length of drilling and have found that stopping short of the posterior aspect of the anterior ring outline is adequate, taking care to be lined up in the middle with regard to the cranial-caudal direction.…”
Section: Fixation To the Atlasmentioning
confidence: 99%